Preganglionic sympathetic neurones, innervating the guinea pig adrenal medulla, immunohistochemically contain choline acetyltransferase and also leu-enkephalin - Colombo-Benkmann, Mario; Heym, Christine; Schemann, Michael (Neuroscience letters, 1995)
Applying retrograde neuronal tracing combined with double labelling immunofluorescence, preganglionic nerve cell bodies in the intermediate grey matter of the guinea pig thoracic spinal cord, projecting to the adrenal gland, co-exhibited immunolabelling for choline-acetyltransferase (ChAT) and sometimes, also for leu-enkephalin. Likewise, ChAT-immunoreactive nerve fibers, forming a dense meshwork in the adrenal medulla, partly contained immunostaining also for leu-enkephalin. Some of the intramedullary nerve cell bodies were ChAT-positive but were non-reactive for leu-enkephalin. The findings provide evidence for an extrinsic (preganglionic) and an intrinsic (postganglionic) cholinergic nerve system in the guinea pig adrenal medulla, the preganglionic syste, utilising leu-enkephalin as co-mediator.
Elektronische Reproduktion der Druck-Ausgabe 14. Januar 2000
Gesehen am 06.11.2025